Macroeconomics : principles and applications - Hall, Robert Ernest, 1943- (South-Western College, 2001)
This book is divided into six parts: Preliminaries; Macroeconomics: basic concepts; Long-run macroeconomics; Short-run macroeconomics; Money, Prices, and the macroeconomics; Macroeconomic Policy; and Using all the theory.